Factors associated with physical, psychological and functional outcomes in adult trauma patients following Road Traffic Crash: A scoping literature review. (December 2019) - Alharbi, Rayan; Mosley, Ian; Miller, Charne; Hillel, Stav; Lewis, Virginia
Abstract: Objective: Road Traffic Crashes (RTCs) are a major cause of disability globally, with millions of people being injured or disabled each year. This study aims to identify the factors reported in the literature that are associated with physical, psychological and functional outcomes of adult trauma patients following an RTC. Methods: A scoping literature review was conducted. Peer-reviewed articles were retrieved from MEDLINE, EMBASE, and CINAHL. These databases were chosen as the MeSH and Emtree thesauri allow for high specificity searches. Moreover, these databases index the major biomedical/health journals in the field. Results: Thirty-one studies from 10 countries are reported in a PRISMA chart and summarized in a matrix. This review identified a number of factors that are clustered into six categories; (i.) injury characteristics and hospital predictive factors; (ii.) demographic factors; (iii.) family and social support; (iv.); compensation system process and fault in the RTC (v.); pre-injury health status. A final category was used to represent the range of (vi.) psychological and functional outcomes. Conclusion: These findings highlight the multiple and diverse contributors that influence a person's outcomes following an RTC. These factors are intrinsic and extrinsic and commence from the time of injury as well as highlighting the importance for ongoing support after acute care discharge to enable a quick return to optimal wellbeing. Research examining RTC outcomes must integrate information about the crash response and health care system while simultaneously measuring other factors to appropriately quantify the relative contribution of each variable to psychological and functional outcomes. Highlights: This literature identified factors associated with physical and psychological morbidity following RTCs People aged 40-49 years and patients with low education level had poorer recovery Lower perceived social support and social life limitations were independent predictors of psychological disability following an RTC Long-term pain was an independent predictor of neuropsychological and psychosocial risk Anxiety, depression, a reduced rate of returning to work, and longer recovery times have been associated with the use of injury compensation schemes